Predictive Business Intelligence Framework for Evaluating the Financial Viability of Accountable Care Organizations ble Care Organizations (ACOs) within U.S. Public Health Systems (The Science Post, 2026)
The transition from fee-for-service to value-based payment models has positioned Accountable Care Organizations (ACOs) as central pillars of U.S. public health system reform. However, many ACOs struggle with financial sustainability due to unpredictable shared savings, high initial infrastructure costs, and complex patient risk stratification. This study addresses the gap in real-time, predictive tools for assessing ACO financial viability. The purpose is to design and validate a Predictive Business Intelligence (BI) framework that integrates machine learning forecasting with operational financial metrics. Using a quantitative, design-based research methodology, we simulate five years of Medicare Shared Savings Program data across 12 public health system ACOs. Key findings indicate that a hybrid model combining random forest regression for cost prediction and Monte Carlo simulation for risk-adjusted revenue forecasting achieves 89.4% accuracy in predicting financial viability 18 months in advance. The conclusion underscores that predictive BI frameworks can reduce financial uncertainty, improve resource allocation, and enhance patient outcomes, offering a replicable model for public health administrators.